1998
DOI: 10.1152/ajpheart.1998.274.6.h1988
|View full text |Cite
|
Sign up to set email alerts
|

Water channel proteins in rat cardiac myocyte caveolae: osmolarity-dependent reversible internalization

Abstract: We show by confocal immunofluorescence microscopy that the water channel protein aquaporin-1, not previously identified within cardiomyocytes, localizes at 20 and 37°C to rat cardiomyocyte sarcolemmal caveolar membrane and subsarcolemmal cytoplasm of primary atrial myocyte cultures, dissociated atrial and ventricular myocytes, and in situ cardiomyocytes of atrial and ventricular frozen sections. Confocal immunofluorescence microscopy shows that the normal in situ colocalization of the quasi-muscle-specific cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 27 publications
7
57
0
Order By: Relevance
“…Our observation that AQP-1 is expressed on the cell membranes of myoepithelial cells that surround the acini of salivary glands has intriguing parallels in the observations of AQP expression in the cell membranes of other excitable contractile cells, including those of smooth muscle cells (Gannon et al, 2000;Shanahan et al, 1999), cardiac muscle cells (Page et al, 1998), and the sarcolemma of fast-twitch skeletal muscle fiber (Frigeri et al, 1998). AQP-1 has been shown to mediate accelerated smooth muscle volume changes in response to altered external osmolarity (Shanahan et al, 1999), suggesting that variation in cell volume mediated by AQP-1 may contribute to contraction and/or variation in tone of vascular smooth muscle (Shanahan et al, 1999).…”
Section: Role Of Aqp-1 In Myoepithelial Cell Functionsupporting
confidence: 67%
“…Our observation that AQP-1 is expressed on the cell membranes of myoepithelial cells that surround the acini of salivary glands has intriguing parallels in the observations of AQP expression in the cell membranes of other excitable contractile cells, including those of smooth muscle cells (Gannon et al, 2000;Shanahan et al, 1999), cardiac muscle cells (Page et al, 1998), and the sarcolemma of fast-twitch skeletal muscle fiber (Frigeri et al, 1998). AQP-1 has been shown to mediate accelerated smooth muscle volume changes in response to altered external osmolarity (Shanahan et al, 1999), suggesting that variation in cell volume mediated by AQP-1 may contribute to contraction and/or variation in tone of vascular smooth muscle (Shanahan et al, 1999).…”
Section: Role Of Aqp-1 In Myoepithelial Cell Functionsupporting
confidence: 67%
“…AQP -1, -4, and -6 seems to play different roles in myocardial infarction (MI) in mouse hearts. While the time dependent pattern of the observed up-regulated expression of AQP4 in MI coincides with that of ME and cardiac dysfunction, the expression of AQP1 and AQP6 persistently increase [4].One of the first reports of aquaporins in heart revealed that AQP1 colocalizes with Caveolin-3 at 20°C and 37°C in rats [7]. Interestingly, when rat cardiac myocytes were exposed to hypertonic media AQP1 was reversibly internalized [7].…”
mentioning
confidence: 73%
“…One of the first reports of aquaporins in heart revealed that AQP1 colocalizes with Caveolin-3 at 20°C and 37°C in rats [7]. Interestingly, when rat cardiac myocytes were exposed to hypertonic media AQP1 was reversibly internalized [7].…”
Section: Editorial Textmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, AQP5 present in lipid rafts in rat parotid glands is translocated to the apical plasma membrane upon the stimulation of acetylcholine receptors of the glands (43). In the rat cardiac myocytes, AQP1 colocalizes with caveolin under the isotonic condition (44). Upon exposure of myocytes to hypertonic medium, AQP1 is dissociated from caveolin and internalized into the intracellular compartments.…”
Section: Localization Of Aqp1 In Lipid Raftsmentioning
confidence: 94%